Acute corticonuclear tract ischemic stroke with isolated central facial palsy - Wolf, Marc; Rausch, Hans-Werner; Eisele, Philipp; Habich, Sonia; Platten, Michael; Alonso, Angelika (Journal of stroke and cerebrovascular diseases, 2019)
Objective The clinical distinction between habitual facial asymry, early stage peripheral facial palsy, and isolated central facial palsy is sometimes difficult. The diagnosis of acute central facial palsy is of importance to identify patients for stroke work-up and appropriate treatment. We aimed to evaluate the prevalence and localization of acute ischemic lesions associated with isolated central facial palsy.Methods We screened our stroke database for patients presenting with isolated central facial palsy related to ischemic stroke between 2012 and 2017. All identified patients were comprehensively characterized including magnetic resonance (MR) diffusion-weighted imaging (DWI). Results We identified four out of 5169 patients (one male; 62-83 years) with isolated facial palsy as a result of acute ischemic stroke (NIHSS 1-2). All four had circumscribed DWI lesions in different regions of the corticonuclear tract in different areas with different etiologies. Conclusion Isolated central facial palsy is a rare manifestation of acute ischemic stroke and may be missed if clinical suspicion is not raised. MR-DWI identifies small ischemic lesions in the corticonuclear tract, which results in appropriate diagnostic work-up and secondary prophylaxis.